Focus on value : - Grant, James L. (Wiley, 2001)
Economic profit is one of the most useful managerial tools as well as a key to understanding the valuation of companies. Focus on Value is an outstanding piece of work. It captures the full spectrum of the Metric Wars without ever confusing the reader. The serious student of economic profit will be richly rewarded by reading this excellent book from cover to cover.